Transcutaneous Immunization Studies in Mice Using Diphtheria Toxoid-Loaded Vesicle Formulations and a Microneedle Array - Ding, Zhi (Springer US, 2010)
PURPOSE: To determine the immunogenicity of diphtheria toxoid (DT) formulated in two types of vesicles following transcutaneous immunization (TCI) of mice onto microneedle array-treated skin. METHODS: DT-containing cationic liposomes or anionic surfactant-based vesicles were prepared by extrusion and sonication. The physicochemical properties were characterized in terms of size, ζ-potential, vesicle elasticity and antigen association. TCI was performed by applying formulations onto intact or microneedle array-pretreated mice skin, using cholera toxin as an adjuvant. Subcutaneous and intradermal immunizations were as control. Immune responses were evaluated by IgG and neutralizing antibody titers, and the immune-stimulatory properties were assessed using cultured dendritic cells. RESULTS: Stable DT-containing cationic liposomes (∼150 nm) and anionic vesicles (∼100 nm) were obtained. Incorporation of Span 80 increased liposome elasticity. About 90% and 77% DT was associated with liposomes and vesicles, respectively. TCI of all formulations resulted in substantial antibody titers only if microneedle pretreatment was applied. Co-administration of cholera toxin further augmented the immune responses of TCI. However, vesicle formulations didn’t enhance the immunogenicity on either intact or microneedle-treated skin and showed low stimulatory activity on dendritic cells. CONCLUSIONS: Microneedle pretreatment and cholera toxin, but not antigen association to vesicles, enhances the immunogenicity of topically applied DT.